Interim report of operations and statement of accounts for the period September 1987 - September 1988 - National Maritime Authority (Lagos, Nigeria : National Maritime Authority, 1988)
This is a report of the Nigerian Maritime Authority, spanning twelve months from September 1987 to September, 1988. It covers the key activities of the organization and the financial statements for the review period
osc 05/03/2019
Arch
Keywords: Annual reports; Maritime; Nigeria